QUADRATIC OPTIMAL REGULATOR PROBLEM OF DYNAMIC GAME FOR DESCRIPTOR SYSTEM - Salmah, . (2011)
Abstract. In this paper the noncooperative linear quadratic game problem will be considered. We present necessary and sufficient conditions for existence of optimal strategy for linear quadratic continuous non-zero-sum two player dynamic games for index one descriptor system. The connection of the game solution with solution of couple Riccati equation will be studied. In noncooperative game with open loop structure, we study Nash solution of the game. If the second player is allowed to select his strategy first, he is called the leader of the game and the first player who select his strategy at the second time is called the follower.A stackelberg strategy is the optimal strategy for the leader under the assumption that the follower reacts by playing optimally.